THE ROLE OF PHONETIC GAMES IN THE DEVELOPMENT OF PHONETIC SKILLS IN STUDENTS OF A SECONDARY SCHOOL AT THE PRIMARY STAGE OF LEARNING THEIR NATIVE LANGUAGE - Abumalik Mutallievich Dedakhanov (The Conference Hub, 2026)
This article presents research on the impact of phonetic games on speech development in primary school students. These games not only contribute to improved performance but also enhance students' motivation and engagement in the language being studied. Developing phonetic competence is a cornerstone of global linguistic education, determining the success of foreign language acquisition. This task is particularly relevant in language teaching, as accurate pronunciation and phonetic accuracy ensure effective communication. Therefore, the study of general phonetics, which explores the universal patterns of phonetic systems and their properties, encompassing the entire process of generating and perceiving oral and written speech, is of considerable interest.
Keywords: speech skills, phonetic skills, stress, intonation, phonemes, syllable, speech rate, intonation contours, speech, articulation, acoustics.